Hidden Hearing Loss? No Effect of Common Recreational Noise Exposure on Cochlear Nerve Response Amplitude in Humans - Grinn, Sarah K.; Wiseman, Kathryn B.; Baker, Jason A.; Le Prell, Colleen G. (Frontiers in Neuroscience, 2017)
This study tested hypothesized relationships between noise exposure and auditory deficits. Retrospective assessment of potential associations between noise exposure history and performance on an audiologic test battery and prospective assessment of potential changes in performance after new recreational noise exposure were completed. METHODS: 32 participants (13M, 19F) with normal hearing (25-dB HL or better,0.25-8 kHz) were asked to participate in 3 pre- and post-exposure sessions including: otoscopy, tympanometry, distortion product otoacoustic emissions (DPOAEs) (f2 frequencies 1-8 kHz), pure-tone audiometry (0.25-8 kHz), Words-in-Noise (WIN) test, and electrocochleography (eCochG) measurements at 70, 80, and 90-dB nHL (click, and 1-4 kHz tone-bursts). The first session was used to collect baseline data, the second session was collected the day after a loud recreational event, and the third session was collected 1-week later. Of the 32 participants, 26 completed all 3 sessions. RESULTS: The retrospective analysis did not reveal statistically significant relationships between noise exposure history and any auditory deficits. The day after new exposure, there was a statistically significant correlation between noise “dose” and WIN performance overall, and within the 4-dB signal-to-babble ratio. In contrast, there were no statistically significant correlations between noise dose and changes in threshold, DPOAE amplitude, or AP amplitude the day after new noise exposure. Additional analyses revealed a statistically significant relationship between TTS and DPOAE amplitude at 6 kHz, with temporarily decreased DPOAE amplitude observed with increasing TTS. CONCLUSIONS: There was no evidence of auditory deficits as a function of previous noise exposure history, and no permanent change in audiometric, electrophysiologic, or functional measures after new recreational noise exposure. There were very few participants with TTS the day after exposure - a test time selected to be consistent with previous animal studies. The largest observed TTS was approximately 20-dB. The observed pattern of small TTS suggests little risk of synaptopathy from common, recreational noise exposure, and that we should not expect to observe changes in evoked potentials for this reason. No such changes were observed in this study. These data do not support suggestions that common, recreational noise exposure is likely to result in “hidden hearing loss”.